Praktik atau Pelaksanaan Supervisi Pendidikan Islam Berbasis Teknologi di Era 5.0 Smart Society - Ach. Syafiul Anwar; Ahmad Fatah Yasin; Indah Aminatus Zuhriyah (EduInovasi: Journal of Basic Educational Studies, 2024)
This research investigates the role of madrasa heads in implementing technology-based education in the Era of Society 5.0 in Indonesia. Madrasah heads have an important responsibility in leading educational transformation to ensure the relevance and quality of learning. This study uses an observational approach to explore effective leadership strategies in adopting educational technology, such as e-learning and other digital-based learning methods. Observation results show that structured supervision and coaching teachers in the use of technology are the keys to improving the quality of learning in madrasas. Technology adoption also contributes to the development of technology adaptation, creativity and communication skills that are important for students in the digital era.